CONFLICT OF INTERESTS’ REGULATION ON ELECTED OFFICIALS - Marta-Claudia CLIZA (Challenges of the Knowledge Society)
This article sheds an overview of the different perspectives that judicial courts grant regarding the same concept, namely the conflict of interest in relation to the elected officials. We will also analyze the ambiguous and contradictory interpretations that the Romanian legislation has to offer on the issue.